2023
DOI: 10.18805/ag.r-2581
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanobiotechnology in Enabling Plants to Overcome Water-logging Stress: A Review

Abstract: Abiotic stresses adversely affect plant growth and ultimately crop productivity. Of these, water-logging is the most widespread and most commonly experienced stress factor. While water is essential for all plant growth and development processes, waterlogging is an obstacle to sustainable agriculture. Recent FAO reports indicate that universal crop production must be enhanced by 70% by 2050 in order to meet the growing demand for food by an estimated 2.3 billion people. As demand for food increases, there is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…8 Nanozymes have diverse advantages, including low usage and high efficiency in crop enhancement. Thus, nanozymes have been used to alleviate plant abiotic stress in various ways, 9 such as reducing stress caused by salinity, 10 temperature fluctuations, 11,12 drought, 13 waterlogging, 14 soil heavy metal pollution, 15 etc. For instance, Chen et al found that nano Fe 2 O 3 could increase the photosynthesis and biomass of peanuts.…”
Section: Introductionmentioning
confidence: 99%
“…8 Nanozymes have diverse advantages, including low usage and high efficiency in crop enhancement. Thus, nanozymes have been used to alleviate plant abiotic stress in various ways, 9 such as reducing stress caused by salinity, 10 temperature fluctuations, 11,12 drought, 13 waterlogging, 14 soil heavy metal pollution, 15 etc. For instance, Chen et al found that nano Fe 2 O 3 could increase the photosynthesis and biomass of peanuts.…”
Section: Introductionmentioning
confidence: 99%